Peningkatan Kualitas dan Daya Awet Ikan Asap Melalui Teknologi Pengasapan Mekanis “Cabinet Smoke” di Paguyuban Asap Sejahtera, Pasuruan: Improving the Quality and Durability of Smoked Fish Through Mechanical Smoking Technology “Cabinet Smoke” at the Asap Sejahtera Association, Pasuruan - Setijawati, Dwi; Sugiyanto, Sugiyanto; Yahya, Yahya; Nurhadi, Iwan; Anggraini, Elok; Rifaweura, Muhammad Alifan Hakim; Riawan, Iqbal Muhammad Rafi; Al Amin, Mochammad Hafidz; Hidayatullah, Muh. Nurdin; Iksan, Muhammad Adhitya; Hibatillah, Muhammad Fakhri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The smoked fish industry in Pasuruan Regency, particularly on the Nguling coast, faces challenges related to product quality and durability, which makes it less competitive in the broader market. The Asap Sejahtera Association, whose members are primarily women, still uses traditional smoking methods. The products produced are easily damaged and not uniform in color and taste. This condition limits the distribution of smoked fish products outside the region, reducing their competitiveness. The Doktor Mengabdi Program aims to enhance the quality and shelf life of smoked fish products using advanced technology, specifically a Mechanical Smoking Furnace equipped with the "Cabinet Smoke" System. This technology is expected to overcome problems such as case hardening and high water content, which often reduce product quality. In addition to technical improvements, this program offers training and mentoring in business management to female smokers, enabling them to better prepare for market dynamics and increase their family income. This initiative not only focuses on product quality but also on empowering women in the Pasuruan fisheries sector.